DIGITAL BUSINESS MODELS AS A FACTOR IN ENSURING THE COMPETITIVENESS OF ENTERPRISES - Ольшанська, Олександра В.; Бондаренко, Богдан С. (Journal of Strategic Economic Research, 2024)
Today, digital business models are becoming a determining factor in the success and victory of enterprises in the competitive struggle. Scientific and technological progress, rapid development of information technology and globalization are driving the business world to actively implement digitalization and digital transformation processes to ensure the competitiveness and competitive advantages of business structures and their sustainable development. The purpose of the study is to determine the role of digitalization in modern business, to characterize modern digital business models to determine their features and capabilities and the feasibility of their use in enterprises and organizations. Research methods used in the study: systematization, classification, comparison, analysis, synthesis, induction, deduction. The article analyzes the definitions of the concept of "business model", considers the classification of digital business models and describes the main digital business models used in companies. The advantages and disadvantages of digitalization of business entities are considered. The use of information and communication technologies and e-commerce at Ukrainian enterprises is analyzed. Every company has a business model, regardless of how clearly it is defined. A business model is considered digital if it uses digital technologies that affect the creation of customer value and revenue generation. Today, there are quite a few types of digital business models used by enterprises. The choice of a particular model depends on the specifics of the company's activities, the peculiarities of production and sales of products, etc. Some companies use a combination of business models. The digitalization and digital transformation of business models will allow enterprises and organizations to increase their competitiveness and ensure high-level competitive advantages in domestic and foreign markets. The digitalization of business models in Ukraine is quite active. Almost all domestic enterprises have access to the Internet, and a fairly large share of businesses have created their own websites, purchase cloud computing services, and generate revenue from e-commerce.